Effectiveness of integrating icts in trained peer-review techniques: improvement in ecuadorian secondary efl learners' quality of writing - Franco Ponce, Rosa Monserratt (2021)
Writing tends to be an isolated and complex skill inEnglish as a Foreign Language classrooms. However, trained peer-review techniques have appeared as a solution to share knowledge and to create more confidence among students in their writing performance. In that way, this quantitative research project aims to demonstrate the effectiveness of these peer-review techniques integrating Information and CommunicationsTechnology tools in English as a Foreign Language sophomore students from a non-bilingual private high school in Pedro Carbo city. This study includes fifty-four EFL learners aged 15-16, both females and males. The participants were divided into three groups. The experimental group (writers) received corrective feedback from their peers, the second one, revisors, gave comments to the writers’ workand the control group that received traditional teachers’ feedback. The communication and cooperation between revisors and writers were kept anonymous to prevent conflicts and biased interactions. Theinstruments applied were adapted writing rubrics for B1, checklist, pre-task, second task,Google Docs,Liveworksheet,and Padlet where all participants collaborated.